REPRODUCTION BIOLOGY EASTERN LITTLE TUNA Euthynnus affinis IN THE SUNDA STRAIT - Vera Ardelia; Yon Vitner; Mennofatria Boer (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Eastern little tuna is small pelagic fish that has high economic value. Fishing effort of the eastern little tuna for the last eight years have also exceeded the optimum level. To ensure the sustainability of the pelagic fish resources, it is necessary to perform the management efforts. This study was to observe reproductive Biology of the eastern little tuna, as one of the necessary information in the management of fishery resources. Fish -samples were collected from the catch of local fishermen in April-August 2015. Based on T test (α = 0,05), the eastern little tuna males and females showed positive allometric growth patterns. Average size of the first time caught fish for the female (308,37 mm) and male (280,63 mm) was smaller than that observed in those first time maturity gonads (ranging 407-408 mm for female and 438-440 mm for male). The eastern little tuna spawn gradually or partially (partial spawner), and have high reproductive potential with fecundity ranged 17.814-560.792 eggs (average fecundity: 109.807) in fish of 285-630 mm body length. The gonad maturity level of the eastern Little Tuna is dominated by Gonad maturity level I and II,(immature). The value of gonad maturity for the female level is about 0,0769-0,6879 and the male is 0,1913-0,3000.